Rhythm in film and symbolism by Susanne Langer - Fernández Trujillo, María del Carmen (2023)
This research analyzes rhythm in fiction films based on the notion of rhythm in the arts of philosopher Susanne Langer and her theory of symbolism. Unlike previous studies on rhythm in film, conducted from mathematical perspectives with metrics of time, proportions and frequencies of montage shots, this study aims to demonstrate that the phenomenon of rhythm in film can also be analyzed from the philosophy of art, in this case, from the symbolism of Langer. In this regard, she considers that rhythm in the arts is recreated in the relationship of the tensions of a work to promote the symbolism of feelings as a whole. The results show that there are up to four recurrent forms of relationships when representing tension scenes (or dramatic tension) and that these successive relationships of tensions are represented by the filmmaker in a conscious and reflexive way until the significance of feelings in the whole film is achieved. This study is a new way of analyzing rhythm in film art, as well as a contribution that highlights some techniques for managing rhythm and symbolizing feelings by the audiovisual filmmaker.